Observation of Intramural Fibroid Expulsion on MRI after Uterine Artery Embolization. (14th August 2021) - Matsushima, Hisakazu; Kageyama, Ken; Yamamoto, Akira; Jogo, Atsushi; Sohgawa, Etsuji; Nota, Takehito; Murai, Kazuki; Ogawa, Satoyuki; Nakano, Mariko; Shimono, Taro; Miki, Yukio
Abstract : Uterine artery embolization (UAE) is a type of noninvasive treatment for symptomatic uterine fibroids. One of the complications of UAE is fibroid expulsion. Here, we report a case of a 45-year-old woman who underwent UAE for an intramural fibroid, which resulted in fibroid expulsion. To the best of our knowledge, there are only few reports of expulsion of intramural fibroids. The process of fibroid protrusion from the myometrium into the uterine cavity was depicted on magnetic resonance imaging (MRI) in this case. We discuss the risk factors and mechanisms of fibroid expulsion after UAE.